Peran Pendidikan Pesantren Dalam Membentuk Perilaku Sehat, Kematangan Spiritual Dan Peduli Lingkungan - Mas'ud (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2022)
Researchers collect data with documentation techniques about the role of Islamic boarding school education in shaping healthy behavior, spiritual maturity and caring for the environment. The study results conclude that the pesantren education model since the emergence of covid 19 in 2019 to 2022 has innovated and internalized the development of learning based on healthy living behaviour, spiritual maturity and environmental care. The attitude of healthy living behaviour places the basis on intelligence, knowledge, noble character, personality and concern for others and the environment. Spiritual maturity includes student behaviour in student interpersonal interactions, such as being honest, disciplined, confident, caring and responsible for oneself and family. Keywords: Islamic boarding school education, healthy living behaviour, spiritual maturity and care for the environment.